THE LEGAL LABYRINTH OF ICAFE: HOW JURISPRUDENCE ENDED THE CONFLICT OVER THE PARAFISCAL CONTRIBUTION - Piedra Matsenko, Yelena (2025)
The jurisdictional conflict and query within the legal community regarding the collection of the ICAFE parafiscal contribution are addressed. It identifies three positions: that of Public Law, which classifies it as parafiscal and associates it with the contentious-administrative jurisdiction; that of Agrarian Law, which interprets it as "agrarian parat-tax matter"; and that of Civil Law, which views it as a monetary obligation. The analytical conclusion of the essay is that the agrarian jurisdiction is the competent one.